Syntactic Theory - Poole, Geoffrey 1969- (Palgrave Modern Linguistics, 2008)
Clear, practical and accessible, Syntactic Theory introduces students to theory building and evaluation through Government-Binding Theory. Now fully updated, this second edition features new chapters on the Minimalist Program, expanded chapters on Phrase Structure and Functional Categories and extensively revised end-of-chapter exercises